Statistical Analysis of Small Structures in Rotated Crustal Blocks Near the Husavik-Flatey Fault, Northern Iceland - Hummel, Natalie (Carleton Digital Commons, 2020)
The right lateral Húsavík-Flatey fault, in and just off the coast of northern Iceland, provides a unique opportunity to observe an oceanic transform fault on land. Structural and paleomagnetic measurements from lavas and dikes on Flateyjarskagi peninsula indicate that rocks adjacent to the fault have rotated clockwise more than 100°. I examine the effect of this rotation on the orientations of small faults and vein zones near the transform. I also use patterns in small-scale data to build on models of the style of deformation surrounding the fault. Previous studies provide constraints on the extent of rotation across Flateyjarskagi, which I use to estimate the expected orientations of rotated structures. The orientations of some small faults are consistent with expected rotations, but many structures appear to post-date rotation. Rotation of an older subset of the small faults on Flateyjarskagi accounts for patterns that have previously been attributed to variations in the stress field near the transform.